Free Higher Education: Regressive Transfer or Implicit Loan? - Vandenberghe, Vincent (Les Cahiers de Recherche du Girsef, 2005)
Should access to higher education remain ‘free’? Theoretical answers to this question are at least twofold. First, public higher education is said to be regressive as a privileged minority profits from extra human capital, and all the private benefits it generates, while the general public foots the bill. A frequent reply is that higher education students enjoying ‘free’ access are implicitly borrowing public money that they pay back when entering the labour market, via progressive income taxes. Using a simple lifecycle framework this paper produces realistic estimates of how much graduates are likely to ‘reimburse’ society via income tax. Using Belgian data on higher education public expenditure and income taxes paid by both graduates and nongraduates over their lifetime, we show that the implicit reimbursement rate ranges from 37% to 95%. It is much higher for bachelors than master graduates, and for males.